أسس الثقافة الإجتماعية والسيكولوجية في إعداد المواد التعليمية لغير الناطقين بالعربية - Fina Aunul Kafi (Al-Fusha : Arabic Language Education Journal, 2020)
In the preparation of Arabic teaching materials for schools need to be adjusted to the socio-cultural and psychological aspects so as to minimize the difficulties of students in understanding the Arabic language lessons presented. Characteristics of good Arabic teaching materials include balanced material between the four competencies and grammar and are adapted to the local conditions of the students. In addition, the relevance of teaching materials is largely influenced by the perception of Arabic teachers on student needs and success in learning. This study aims to discover how the socio-cultural and psychological aspects of preparing Arabic language teaching materials. This research uses descriptive qualitative methods. The results of this study indicate that there is a need for harmony between socio-cultural and psychological aspects with the condition of students to increase success in learning.